PENGARUH MANAJEMEN MODAL KERJA TERHADAP TINGKAT LIKUIDITAS PERUSAHAAN PADA INDUSTRI SEMEN YANG TERDAFTAR DIBURSA EFEK INDONESIA - Trilia Rahayu; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aimed to determine the effect of working capital manajemen ofliquidity level on cement companies listed in Indonesia Stockt Exchange.Independent varibles was used this study is working capital. Working capital wasmeasured with used working capital turn over, while the dependent variables isliquidity was measured with used current ratio.The sample in this study selected based on specific criteria usingpurposive sampling metode. Obtained a samples of 3 companies have financialstatement period 2003-20013, so that obtained of 33 observation.Analysis of the data used in this study is simple regression analysis wereprocessed with SPSS. From the test simple regression analysis showed thatworking capital turn over the have significant negative effect on current ratio.Keywords: working capital, likuidity, working capital turn over, current ratio.